Effect of essential oils of copaiba and oregano in substitution of synthetic antioxidants in Tambaqui fish meat balls (Research, Society and Development, 2020)
The objective of the present experiment was to evaluate the effects of including the essential oil of copaiba and oregano as a possible replacement for synthetic butylated hydroxytoluene (BHT) additives in fish meat ball. PH, cooking loss, texture, color, sensory acceptability and chemical composition were evaluated. The addition of oregano essential oil had an effect on the color of the fish meat ball (P